Characterization of fluid mixtures at high pressures using frequency response of microcantilevers - Eris, Gamze; Baloch, Shadi Khan; Bozkurt, Asuman Asikoglu; Jonas, Alexandr; Kiraz, Alper; Alaca, B. Erdem; Erkey, Can (ELSEVIER SCIENCE SA, 2017)
The frequency response of ferromagnetic nickel microcantilevers immersed in binary mixtures of carbon dioxide (CO2) and nitrogen (N-2) at 308 K and pressures up to 23 MPa was investigated. Experimental data were analyzed using the model developed by Sader for a clamped oscillatory beam immersed in a fluid and a very good agreement between the measured resonant frequencies and quality factors (Q factors) and the theoretical predictions of the model with cantilever characteristic parameters regressed from experimental data was observed. This suggested that the data could be used to simultaneously measure the density and the viscosity of fluid mixtures over a wide range of pressures. Subsequently, density and viscosity of binary mixtures of CO2 and N-2 were determined using N-2 as the reference fluid and compared to the predictions of Gerg equation of state and Chung equation, respectively. For the studied fluids with different compositions, the average relative difference between the experimental density values and the values predicted using Gerg equation of state and NIST database ranged from 1.0 to 13%. The average relative difference between the experimental viscosity values and the values obtained using Chung equation and NIST database ranged from 2.4 to 15%. Since the resonant frequency and Q factor were found to vary with composition at a fixed temperature and pressure, the technique can in principle also be used to measure the composition of a binary mixture at a fixed temperature and pressure. The study represents the first systematic attempt to use microcantilevers for the characterization of high-pressure fluid mixtures and paves the way for devising portable sensors for in-line monitoring of thermophysical properties and composition of fluid mixtures under a wide range of environmental conditions. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Microcantilever; Frequency response; Binary gas mixtures; Density; Viscosity; Resonant frequency; Quality factor; High pressure; Carbon dioxide; Nitrogen; MICRO-CANTILEVERS; VISCOUS FLUIDS; GASES; DISSIPATION; ARRAY; Engineering; Instruments & Instrumentation